Mitochondrial DNA (mtDNA) in brain samples from patients with major psychiatric disorders: Gene expression profiles, MtDNA content and presence of the MtDNA common deletion1. Issue 2 (25th January 2013) - Torrell, Helena; Montaña, Elena; Abasolo, Nerea; Roig, Bàrbara; Gaviria, Ana M.; Vilella, Elisabet; Martorell, Lourdes
Abstract Several lines of evidence support a mitochondrial dysfunction in major psychiatric disorders. The objective of this study was to determine whether mitochondrial DNA (mtDNA) expression or content are implicated in the mitochondrial dysfunction observed in schizophrenia (SCH), bipolar disorder (BD), and major depressive disorder (MDD). MtDNA gene expression and mtDNA content (including the MT‐ND4 deletion) were measured by RT‐qPCR and qPCR, respectively. Post‐mortem brain tissue from 60 subjects, divided evenly into four diagnostic groups (SCH, BD, MDD, and control (C)), was analyzed. MT‐ND1 gene expression was significantly increased in the BD group compared with the C group. MDD and SCH patients showed a similar pattern of mtDNA expression, which was different from that in BD patients. Similarly, a larger number of MDD and SCH patients tended to have the MT‐ND4 gene deleted compared with BD and C subjects. However, no other significant differences were observed in mtDNA gene expression and mtDNA content. Notably, high variability was observed in the mtDNA gene expression and content in each diagnostic group. Previous studies and the present work provide evidence for a role of mtDNA in SCH, BD and MDD. However, further studies with larger patient and control groups as well as by analyzing distinct brain regions are needed to elucidate the role of mtDNA in major psychiatric disorders. © 2013 Wiley Periodicals, Inc.